Spatial and temporal relationships between Eocene sand horizons and iron contamination in stream water in the Thames Basin west of London, UK - Barrott,JJ; Dudeney,AWL; Mason,PJ (Geochemistry-Exploration Environment Analysis, 2014)
Analyses of stream water samples associated with Tertiary (Eocene) sands of the Bracklesham Formation 30–60 km west of London showed numerous occurrences of groundwater containing elevated iron(II) concentrations (1–15 mg/l Fe), which oxidise to red-brown ferrihydrite in localised wetlands and streams and join onward flows towards the River Thames. GIS mapping of iron concentrations in relation to topographical and geological data within a 20×30 km project area indicated some 168 km of iron-contaminated water.The results are consistent with downward permeation of groundwater through contained Camberley, Windlesham and Bagshot sand horizons and predominant W-E groundwater flow of up to 35 km in the Bagshot horizon, which rests on impermeable London Clay. Glauconite, comprising up to 70% of the sand near the base of the Windlesham horizon, apparently provides the main source of soluble iron in the near-anoxic, near-neutral, conditions normally prevailing. Pyrite is also a possible source, especially where quarrying or other excavation releases water from previously isolated volumes, simultaneously causing elevated sulphate and acidity levels via relatively rapid sulphide oxidation. Mechanisms proposed are underpinned through comparison with reports on analogous systems in the UK and abroad.Streams and lakes in the vicinity of seepages are highly visible and of decreased biodiversity. However, because of their natural origin, they are not subject to the same public concern and environmental control as compositionally similar near-neutral water from many former coal mines elsewhere - where iron derives primarily from pyrite. Also, while comparatively persistent, they appear destined for rapid depletion in geological terms: the unusual isolation of the sands until the Quaternary indicates a short leaching period and suggests a reason why iron-rich water from natural ferruginous sands is seldom of sufficient significanc